THE ANALYSIS OF SYNTACTIC ERRORS IN STUDENTS’ EXPOSITION WRITING OF CLASS X AT SMA YAPIP SUNGGUMINASA IN GOWA REGENCY - Rizki Herdiani; Johar Amir; Syamsudduha Syamsudduha (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
The research objectives are: (i) to describe phrase errors found in students’ expository writing of class X at SMA YAPIP Sungguminasa in Gowa Regency; and (ii) to describe sentence errors found in students’ expository writing of class X at SMA YAPIP Sungguminasa in Gowa Regency. The study used a qualitative descriptive design. Data collection techniques are techniques to read, take notes, and interview teachers and students. Data were analyzed by identifying, classifying, explaining, and evaluating. The results showed that (i) phrase errors include four types of prepositional phrase errors: verbal phrase errors, nominal phrase errors, and adjectival phrase errors; (ii) sentence errors include seven types: sentences with no subject, sentences with no subject and no predicate, illogical sentences, pleonasms, conjunctive disappearances, excessive conjunctions, and unnecessary usage of unquestioned words.